Development of Psychological Measurement Tools: Self Regulated Learning Scale (SRLS) - Faruq Faruq; Intan Wahyu Istiqomah; Nureyzwan Sabani; Siti Rahmawati; Kelvin Rivalna; Kumaidi Kumaidi; Muh Bagus Sudinadji (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Self-Regulated Learning or SRL is an important academic performance for every student in completing a series of academic activities and realized by himself, especially in an online learning environment that is not supervised directly by the teacher. This research is an effort to develop a measuring instrument in the form of an SRL scale and called the SRLS based on three aspects according to the theory presented by Zimmerman. The purpose of this study is to produce a student SRL measurement tool in the online learning era in order to find patterns of student involvement in learning that can be applied by students to improve learning achievement. Respondents involved in this study amounted to 408 students of SMP/MTs grades VII to IX. Validation of items through an expert judgment process by experts in psychometry and psychology with the results of the content validity item (CVI) obtained is 0.68 to 1.00 and the reliability test results have a Cronbach alpha value of 0.893. The results of this research will provide benefits to identify patterns of student involvement in learning and generated guidelines for the use of the SSRL measuring instrument.